ERβ-regulated circATP2B1/miR-204–3p/TWIST1 positive feedback loop facilitates epithelial to mesenchymal transition in clear cell renal cell carcinoma - Hu Wang; Yilong Gao; Fengran Guo; Pengfei Zhou; Ziyang Ma; Kui Chi; Jiaqing Ye; Hao Sun; Xingyu He; Bei Shi; Yaxuan Wang; Zhenwei Han (Translational Oncology)
Background: Our previous studies have shown that estrogen receptor beta (ERβ) can promote the progression of clear cell renal cell carcinoma (ccRCC) by downregulating the expression of circATP2B1 and miR-204–3p. Here, we found that ERβ might promote the epithelial-mesenchymal transition(EMT) of ccRCC by modulating the circATP2B1/miR-204–3p/TWIST1(Twist family basic helix-loop-helix transcription factor 1) signaling pathway. Methods: We utilized bioinformatics analysis to determine the clinical significance of TWIST1 in ccRCC. The expression of TWIST1 in ccRCC tissues and cells was examined using immunohistochemistry, real-time quantitative polymerase chain reaction and western blotting assay. Chromatin Immunoprecipitation assay were conducted to validate the relationship between ERβ and TWIST1. Luciferase reporter gene assays were employed to validate the binding targets of TWIST1 and miR-204–3p. The role of TWIST1 in ccRCC was studied through in vitro and in vivo experiments. Transwell assays and wound healing assays were used to assess the impact of TWIST1 on the invasive and migratory abilities of ccRCC cells. Results: Mechanism analysis revealed that miR-204–3p can inhibit TWIST1 by targeting its 3′ untranslated region. Additionally, TWIST1 can promote ERβ transcription by directly binding to transcription factor binding site in the ERβ promoter region, forming a positive feedback loop. These in vitro data were further validated in an in vivo mouse model. Importantly, analysis of data from the TCGA-KIRC database further confirmed the above in vitro/in vivo findings. Conclusions: Together, our results suggest that ERβ/circATP2B1/miR-204–3p/TWIST1 can promote EMT by forming a positive feedback loop, thus promoting the progression of ccRCC. Targeting this newly identified signaling pathway may more effectively control the progression of ccRCC.